2003
DOI: 10.31899/hiv2.1044
|View full text |Cite
|
Sign up to set email alerts
|

Microfinance and households coping with HIV/AIDS in Zimbabwe: An exploratory study

Abstract: Many individuals have contributed to the successful completion of this report and the associated AIMS assessment. I am grateful to each of them. The work in Zimbabwe was dependent upon the high level of cooperation given the research team by the officers and staff of Zambuko Trust. In particular, I would like to thank Tawanda Sibanda, acting executive managing director of Zambuko, who provided advice and assistance. I would also like to acknowledge the cooperation of David Kombanie, former executive managing d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Thus, the replication of this trial in a larger setting should entail partnering with a microfinance institution that is financially stable and whose business model can accommodate Shamba Maisha . Participant concerns around loan repayment are an important ethical consideration; particularly in light of recent findings that microfinance may fail to provide enough income for financially disadvantaged households (Stewart et al 2010 ; Barnes et al 2001 ; Kaboski & Townsend 2008 ). As a result, we plan to consult local and global experts in microfinance in order to ensure that this component meets the needs of the study, and is designed with the potential for scale-up and sustainability is similar settings in East Africa.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the replication of this trial in a larger setting should entail partnering with a microfinance institution that is financially stable and whose business model can accommodate Shamba Maisha . Participant concerns around loan repayment are an important ethical consideration; particularly in light of recent findings that microfinance may fail to provide enough income for financially disadvantaged households (Stewart et al 2010 ; Barnes et al 2001 ; Kaboski & Townsend 2008 ). As a result, we plan to consult local and global experts in microfinance in order to ensure that this component meets the needs of the study, and is designed with the potential for scale-up and sustainability is similar settings in East Africa.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, credit and savings programs have attracted women in unprecedented numbers ( Chen et al, 2005 ). Moreover, women invest their savings in their children, leading to better nutrition and educational outcomes ( Barnes, 2001 ; Barnes, Gaile, & Kibombo, 2001 ; Chen & Snodgrass, 2001 ; Chowdhury & Bhuiya, 2001 ; Khandker, 1998 ; Todd, 1996 ). For example, the Village Savings and Loan Microfinance Program (part of the Livingstonia Synod AIDS Program in Ekwendani, Malawi) establishes and capacitates community-based credit associations open to the whole community; 83% of its participants are women.…”
Section: Solutions Within Reachmentioning
confidence: 99%
“…In Thailand, loans to business partnerships involving an HIV-negative and HIV-positive individual not only improved the economic conditions of PLHA but also reduced stigma and discrimination towards PLHA in the community [ 19 ]. Barnes (2002) examined the effects of microcredit on entrepreneurs in Zimbabwe and found that among HIV-affected households those that accessed microcredit had more sources for securing income, higher proportion of boys in school, and a savings account in a bank, compared to those that did not access credit [ 20 ]. Regarding PLHA on ART, we know of only one qualitative study conducted in Cote d'Ivoire in which the authors found that when PLHA were using appropriate medical treatment, they were capable of engaging in microcredit activities which led to improvements in economic self-sufficiency and provided recipients with psychosocial support [ 21 ].…”
Section: Introductionmentioning
confidence: 99%